PUBLIC POLICIES TO PROMOTE CULTURE AND THE ALLOCATION OF RESOURCES TO THE CREATIVE ECONOMY SECTOR IN THE MUNICIPALITY OF CÁCERES/MT - Piveta, Ana Paula da Silva; de Almeida, Edir Antonia; da Silva, Vanessa Ferreira; Ortiz, Aldo Cesar da Silva; da Costa, Enezio Mariano; de Mello, Nivaldo Teodoro; de Lima, José Ricarte; Oliveira, Raul Angel Carlos (Seven Editora, 2026)
This study aimed to analyze the impacts of resource allocation by public policies promoting culture on the creative economy sector in the municipality of Cáceres/MT, focusing on the Aldir Blanc Law, the Paulo Gustavo Law, and the Aldir Blanc National Policy (PNAB). The research used a qualitative and quantitative approach, through documentary analysis of official data provided by the Ministry of Culture, the Official Gazette of the Municipalities of the State of Mato Grosso, and the Transparency Portal of the Municipality of Cáceres. The work presents an analysis of the distribution and effectiveness of the use of resources at the state level, with a local analytical focus on the municipality of Cáceres/MT, illustrating how these policies were operationalized at the local level. The results indicate that these policies had a significant impact on the execution of the local public budget and contributed to the maintenance and strengthening of creative enterprises, despite the challenges faced in their implementation and adaptation to local realities. It is concluded that public funding for culture presents strategic potential for strengthening the creative economy, and the continuity and improvement of these policies are necessary to expand their positive impacts.